The Impact of Size and Growth Decisions on Turkish Banks' Profitability - Isık, Ozcan; Kosaroglu, Merve; Demirci, Ayhan (International Journal of Economics and Financial Issues, 2018)
The aim of this study is to examine whether bank profitability is affected by the decisions regarding bank size and growth rate. All parameter estimates of regression models are based on fixed-effect panel regression analyses. Our data covers all banks publicly traded on the BIST during the period 2009Q1-2016Q1. Our empirical findings show that there exists a nonlinear (concave) association between different size measures and profitability. In spite of the fact that growth rate tend to be positively associated with profitability, the impact of this variable is not statistically significant. Keywords: Turkish Banking Sector, Bank Size, Growth Rate, Profitability JEL Classifications: C23, E44, G21.